Anatolian origins and diversification of Aethionema, the sister lineage of the core Brassicaceae. Issue 7 (25th July 2017) - Mohammadin, Setareh; Peterse, Kim; van de Kerke, Sara J.; Chatrou, Lars W.; Dönmez, Ali A.; Mummenhoff, Klaus; Pires, J. Chris; Edger, Patrick P.; Al‐Shehbaz, Ihsan A.; Schranz, M. Eric
Abstract : PREMISE OF THE STUDY: The Irano‐Turanian region harbors three biodiversity hotspots and ∼25% of Brassicaceae species are endemic to the region. Aethionema (∼61 species) is the sister lineage to the core Brassicaceae and occurs mainly in the Irano‐Turanian region. The evolutionary important position of Aethionema makes it an ideal reference for broader comparative genetics and genomics. To understand the evolution of Aethionema, and for a broader understanding of crucifer evolution, a time‐calibrated phylogenetic tree and biogeographical history of the genus is needed. METHODS: Seventy‐six plastome coding regions and nuclear rDNA genes, mainly from herbarium material, covering 75% of all Aethionema species, were used to resolve a time‐calibrated Aethionema phylogeny. The different clades were characterized based on four morphological characters. The ancestral area of Aethionema was estimated with historical biogeographical analyses. KEY RESULTS: Three well‐supported major clades within Aethionema were resolved. The ancestral area reconstruction and divergence‐time estimates are consistent with major dispersal events during the Pliocene from the Anatolian Diagonal. CONCLUSIONS: We find that most Aethionema lineages originated along the Anatolian Diagonal, a floristic bridge connecting the east to the west, during the Pliocene. The dispersal of Aethionema correlates with the local geological events, such as the uplift of the Anatolian and Iranian plateaus and the formation of the major mountain ranges of the Irano‐Turanian region. Knowing the paleo‐ecological context for the evolution of Aethionema, in addition to the other lineages of Brassicaceae, facilitates our broader understanding for trait evolution and species diversification across the Brassicaceae.